Production Line Balancing Model to Improve Productivity in a Tempered Glass Processing Company - Escalante Torres, Omar Enrique (2021)
A line balancing model for a tempered glass processing company was developed in this study, aimed at demonstrating how its implementation helps to improve productivity. The model is based on the development of the five steps of the theory of constraints (TOC): identify the constraint, exploit the constraint, subordinate everything to the constraint, elevate the constraint, and check if there is a new constraint. Once the restriction was identified, it was exploited using improvement actions, such as the detection and elimination of mudas (wastes), and the application of the 5S methodology until a production capacity in line with demand was achieved. As economic investments had to be made, a table with a cost structure before and after the implementation of the model was prepared in order to calculate the return on investment (ROI) value to determine that the investment made promoted the increase in productivity.